THE EFFECT OF NON-PERFORMING FINANCING (NPF) AND FINANCING TO DEPOSIT RATIO (FDR) ON RETURN ON ASSETS (ROA) IN ISLAMIC COMMERCIAL BANKS (BUS) IN INDONESIA - Daffa Azura Nurafina; Firdaus (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2026)
This research is motivated by the fluctuations in the ROA value of Sharia Commercial Banks from 2019 to 2023, which indicate that there are several external and internal factors affecting the ROA level. ROA is one of the profitability ratios that can illustrate the return on the use of bank assets when calculating net profit. This research focuses on two internal factors, namely NPF and FDR. The first internal factor that can affect ROA is NPF. NPF is an indicator of the level of financing risk in Islamic banking. The second factor is FDR, which reflects the effectiveness of the bank in distributing financing funds from the total third-party funds collected. The type of research used in this study is a quantitative approach with data analysis techniques using Panel Data Regression Analysis, Classical Assumption Tests, and Hypothesis Testing. In this study, the data used is secondary data. The population in this study consists of 13 Sharia Commercial Banks registered with the OJK. The sample used comprises 11 Sharia Commercial Banks. Based on the results of the research conducted, the following results were obtained: partially, Non Performing Financing (NPF) does not affect Return On Assets (ROA), partially, Financing to Deposit Ratio (FDR) does not affect Return On Assets (ROA), and simultaneously, there is no simultaneous effect between Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on Return On Assets (ROA).